Lactate Kinetics during Exercise in Chronic Obstructive Pulmonary Disease - François Maltais; Sarah Bernard; Jean Jobin; Roger Belleau; Pierre LeBlanc (Canadian Respiratory Journal)
OBJECTIVES: To examine whether the lactate kinetics during exercise are abnormal in patients with chronic obstructive pulmonary disease (COPD) and to evaluate the relationship of lactate kinetics with functional status.